Src kinase modulates the apoptotic p53 pathway by altering HIPK2 localization - Polonio-Vallon, Tilman; Kirckpatrick, Joanna; Krijgsveld, Jeroen; Hofmann, Thomas G. (Cell cycle, 2014)
Non-receptor tyrosine kinase Src is a master regulator of cell proliferation. Hyperactive Src is a potent oncogene and a driver of cellular transformation and carcinogenesis. Homeodomain-interacting protein kinase 2 (HIPK2) is a tumor suppressor mediating growth suppression and apoptosis upon genotoxic stress through phosphorylation of p53 at Ser46. Here we show that Src phosphorylates HIPK2 and changes its subcellular localization. Using mass spectrometry we identified 9 Src-mediated Tyr-phosphorylation sites within HIPK2, 5 of them positioned in the kinase domain. By means of a phosphorylation-specific antibody we confirm that Src mediates phosphorylation of HIPK2 at Tyr354. We demonstrate that ectopic expression of Src increases the half-life of HIPK2 by interfering with Siah-1-mediated HIPK2 degradation. Moreover, we find that hyperactive Src binds HIPK2 and redistributes HIPK2 from the cell nucleus to the cytoplasm, where both kinases partially colocalize. Accordingly, we find that hyperactive Src decreases chemotherapeutic drug-induced p53 Ser46 phosphorylation and apoptosis activation. Together, our results suggest that Src kinase suppresses the apoptotic p53 pathway by phosphorylating HIPK2 and relocalizing the kinase to the cytoplasm.
Published online: 25 October 2013
Gesehen am 12.01.2021